2006
DOI: 10.1007/s10460-006-9013-5
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and information access: Implications for agricultural extension in a rice farming community in northern Vietnam

Abstract: Village communities are not homogeneous entities but a combination of complex networks of social relationships. Many factors such as ethnicity, gender, socio-economic status, and power relations determine one's access to information and resources. Development workers' inadequate understanding of local social networks, norms, and power relations may further the interests of better-off farmers and marginalize the poor. This paper explores how social networks function as assets for individuals and households in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 17 publications
5
73
0
7
Order By: Relevance
“…Formal and informal networks of information-sharing relationships between individuals and groups play important roles in the facilitation of natural resource management, the encouragement or prevention of changes in land use, agricultural innovation, and the diffusion and adoption of farming practices (Bodin et al 2006;Cadger et al 2016;Conley and Udry 2001;Demiryurek 2010;Hoang et al 2006;Isaac 2012;Isaac et al 2014;Klerkx et al 2010;Leeuwis 2004;Matous and Todo 2015;Matouš et al 2013;Prell et al 2009Prell et al , 2010Rogers 2003;Solano et al 2003;Spielman et al 2009Spielman et al , 2011Tengö and Belfrage 2004).…”
Section: Theoretical Framework: Social Network and Spatially Distribmentioning
confidence: 99%
“…Formal and informal networks of information-sharing relationships between individuals and groups play important roles in the facilitation of natural resource management, the encouragement or prevention of changes in land use, agricultural innovation, and the diffusion and adoption of farming practices (Bodin et al 2006;Cadger et al 2016;Conley and Udry 2001;Demiryurek 2010;Hoang et al 2006;Isaac 2012;Isaac et al 2014;Klerkx et al 2010;Leeuwis 2004;Matous and Todo 2015;Matouš et al 2013;Prell et al 2009Prell et al , 2010Rogers 2003;Solano et al 2003;Spielman et al 2009Spielman et al , 2011Tengö and Belfrage 2004).…”
Section: Theoretical Framework: Social Network and Spatially Distribmentioning
confidence: 99%
“…Previous research has shown that the lack of social learning and interpersonal information exchange can result in a lack of awareness and the non-adoption of resourceconserving agricultural practices (Solano et al 2003;Schneider et al 2009;Janssen et al 2006;Pretty and Smith 2004;Bodin and Crona 2009;Bodin and Prell 2011;Leeuwis 2004;Hoang et al 2006;Isaac 2012;Isaac et al 2007;Spielman et al 2011;Conley and Udry 2010). Thus, limiting farmers' mobility may decrease farmers' access to new beneficial techniques in other communities, and farmers may in turn use less-informed and even environmentally harmful practices.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of formal institutions in disseminating necessary agricultural information across vast underdeveloped rural regions has been questioned (Matouš et al 2013b;Douthwaite et al 2001;Leeuwis 2004;Warner 2007;Spielman et al 2009;Gebremedhin and Swinton 2003), and informal social networks and social contact have been recognized as important channels for information-sharing about resource-conserving practices (Rogers 2003;Solano et al 2003;Schneider et al 2009;Ostrom 1990;Folke 2006;Janssen et al 2006;Pretty and Smith 2004;Bodin and Crona 2009;Bodin and Prell 2011;Leeuwis 2004;Hoang et al 2006;Isaac 2012;Isaac et al 2007;Warner 2007;Spielman et al 2011;Conley and Udry 2010;Bartholomay et al 2011). However, communication connections among the inhabitants of areas with less developed infrastructures tend to be geographically constrained, and the potential for the diffusion of beneficial practices between communities is thus limited (Matous et al 2013a;Apicella et al 2012;Urry 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…improving the level of social recognition, reducing the farmers' perception of loneliness and isolation, increasing participation in decision-making, network-building, positive feedback and better relationships with colleagues). In addition, because collaboration is a sort of social network (Kallstrom and Ljung, 2005), it can provide access to information social welfare and better working conditions (Hoang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%